Pengembangan Bisnis Pondok Pesantren Berbasis Sociopreneur Dalam Mewujudkan Semangat Santripreneur - Arianto, Bambang; Handayani, Bekti; Marwati, Marwati (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
The development of the Islamic boarding school business can have a significant impact on the students' self-development in entrepreneurship. In fact, the students not only learn religious knowledge but also learn about linear entrepreneurship with a santripreneur spirit. The Islamic boarding school business development model being developed is social entrepreneurship (sociopreneur) because it is in line with the character of Islamic boarding schools. In community service at the Salafiyah Raudhotutholibin Al-Asy'Ariyah Islamic boarding school, Purwadadi Village, which was held on 10th November 2023, various assistance was provided regarding sociopreneur-based business development. In this training, various knowledge has been provided on designing business ideas in the context of Islamic boarding schools. The success of this activity can be seen from the increasing knowledge and understanding of the students regarding designing business ideas, research and business feasibility studies, production management, business marketing and financial management. From the results of this service activity, it is known that the students have been able to develop a framework for developing the Islamic boarding school business by prioritizing the spirit of social entrepreneurship (sociopreneurship).